Mixed powder, MgO particles, method for producing grain-oriented electrical steel sheet, method for producing MgO particles, and method for producing mixed powder

By controlling the Al and B content in the MgO annealing separator, ensuring the appropriate proportion of tri-coordinated boron, the coating defect problem caused by excessive boron invasion is solved, and the appearance and magnetic characteristics of the orientation electromagnetic steel plate are improved.

CN119768554APending Publication Date: 2025-04-04NIPPON STEEL CORPORATION
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380061907.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-31
Filing Date
2023-08-31
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

When the prior art increases the boron content in the MgO annealing separator to improve the magnetic characteristics and coating characteristics of the oriented electromagnetic steel plate, boron is easily caused to excessive invasion of the steel plate, resulting in coating defects, and suppress insufficient improvement of the appearance characteristics of the coating defects.

Method used

By controlling the Al and B content in the mixed powder, ensuring that the proportion of tri-coordinated boron is within an appropriate range, combined with the appropriate average particle size and firing conditions, MgO particles and mixed powder can be prepared that can inhibit excessive invasion of boron.

Benefits of technology

The generation of coating defects is suppressed, the appearance and magnetic characteristics of the orientation electromagnetic steel plate are improved, and the efficient preparation of the steel plate is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005284904700000181
    Figure BDA0005284904700000181
  • Figure BDA0005284904700000191
    Figure BDA0005284904700000191
  • Figure BDA0005284904700000221
    Figure BDA0005284904700000221
Patent Text Reader

Abstract

The present invention relates to a mixed powder for an annealing separator using MgO as the main component, the mixed powder containing Al and B, the content of Al contained in the whole of the mixed powder being 0.0007 mass% to 0.050 mass%, the content of B contained in the whole of the mixed powder being 0.005 mass% to 0.040 mass%, the B containing a tricoordinated boron, and the balance being Fe and unavoidable impurities, the mixed powder being characterized in that the content of Al contained in the whole of the mixed powder is 0.0007 mass% to 0.050 mass%, and the content of B contained in the whole of the mixed powder is 0.005 mass% to 0.040 mass%. The average particle diameter of the mixed powder is 0.08 [mu] m or more and 9.0 [mu] m or less, and the mixed powder satisfies formula (1). 0.06 < = [Al] / [BO3] lt; 5.00 (1) In the formula (1), [Al] is the Al content (mass%) in the mixed powder, and [BO3] is the content (mass%) of the tricoordinated boron in the mixed powder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a mixed powder, MgO particles, a method for producing a oriented electrical steel sheet, a method for producing MgO particles, and a method for producing a mixed powder. This application claims priority based on Japanese Patent Application No. 2022-137911 filed in Japan on August 31, 2022, and the contents are incorporated herein by reference. Background Art

[0002] Grain-oriented electrical steel sheets are soft magnetic materials and are mainly used as core materials for transformers. Therefore, grain-oriented electrical steel sheets are required to have magnetic properties such as high magnetization characteristics and low iron loss. Iron loss is the power loss consumed as heat energy when the iron core is excited by an AC magnetic field. From the perspective of energy saving, iron loss is required to be as low as possible.

[0003] In the production of grain-oriented electrical steel sheets, a manufacturing method including hot rolling, hot rolled sheet annealing, cold rolling, decarburization annealing and final annealing is usually applied to a steel sheet adjusted to a predetermined composition. Among these processes, in the final annealing process, the steel sheet wound into a coil is annealed at high temperature for a long time to make the crystal orientation converge to the Goss orientation with good magnetic properties (increase the degree of orientation convergence). At this time, an annealing separator is applied to prevent the coil from seizure.

[0004] As the annealing separator applied to the coil, an annealing separator mainly composed of magnesium oxide (MgO) is often used. The reason is that if an annealing separator mainly composed of MgO is used, silicon dioxide (SiO2) on the surface of the steel sheet reacts with MgO during the final annealing, causing tension to act on the surface of the steel sheet, and a forsterite (Mg2SiO4) coating (primary coating) that plays a role in imparting insulation to the steel sheet can be formed. That is, by using an annealing separator mainly composed of MgO, not only can seizure be prevented during the final annealing, but also the magnetic properties of the grain-oriented electrical steel sheet can be improved.

[0005] As described above, in the production of grain-oriented electrical steel sheets, the properties of the grain-oriented electrical steel sheets may vary depending on the annealing separator. Therefore, in recent years, research has been conducted on trace components contained in magnesium oxide contained in the annealing separator. Furthermore, research has been conducted not only on the content of trace components but also on the structure of compounds containing trace component elements in magnesium oxide used as the annealing separator.

[0006] For example, Patent Document 1 discloses a powder for annealing separator, characterized in that it contains 0.04 mass % to 0.30 mass % boron, has magnesium oxide as a main component, and the proportion of tricoordinate boron in the boron is 70 mass % to 95 mass %.

[0007] Patent document 2 discloses a method for producing a powder for an annealing separator, characterized in that a raw material containing either or both of magnesium hydroxide and magnesium carbonate and boron is calcined, and then the ratio of tricoordinate boron is adjusted by adjusting the humidity of the calcined product, wherein the ratio of tricoordinate boron in the boron contained in the powder for an annealing separator is greater than or equal to 70% by mass and less than or equal to 95% by mass.

[0008] Patent documents 1 and 2 both define the proportion of tri-coordinated boron based on the following insights: 1) The coating reaction behavior at high temperature (above 1100°C) affects the purification of impurities; 2) Boron in a tri-coordinated form affects the coating reaction behavior at high temperature; 3) Boron in a tetra-coordinated form not only does not contribute to the purification of impurities, but also invades the steel sheet during high-temperature annealing to form Fe2B, causing repeated bending degradation.

[0009] Prior art literature

[0010] Patent Literature

[0011] Patent Document 1: Japanese Patent Application Publication No. 2017-128772

[0012] Patent Document 2: Japanese Patent Application Publication No. 2020-15982 Summary of the invention

[0013] Problems to be solved by the invention

[0014] Patent Documents 1 and 2 believe that by controlling the amount of boron and the tricoordinate boron ratio in the annealing separator powder, the problems of poor coating appearance and poor purification of impurities in steel caused by insufficient reactivity at high temperatures can be solved. However, the inventors of the present invention have conducted research and found that when the boron content in MgO is increased, the magnetic properties and coating properties (appearance, coating tension) are sometimes improved, but if the boron content is increased excessively, boron excessively penetrates into the steel sheet, sometimes causing coating defects. Therefore, in the techniques of Patent Documents 1 and 2, it cannot be said that the improvement of appearance properties that suppress the generation of coating defects is sufficient.

[0015] The present invention has been completed in view of the above-mentioned problems, and an object of the present invention is to provide a mixed powder, MgO particles, a method for manufacturing a oriented electromagnetic steel sheet, a method for manufacturing MgO particles, and a method for manufacturing a mixed powder for suppressing the generation of coating defects caused by the application of boron and manufacturing a oriented electromagnetic steel sheet with good appearance characteristics.

[0016] Means used to solve problems

[0017] The precipitates (inhibitors) present during secondary recrystallization inhibit the growth of grains other than the Goss orientation. Therefore, the slower the decomposition of the precipitates, the better. Tricoordinate boron is highly reactive at low temperatures and has the effect of improving coating properties and magnetic properties. However, the inventors of the present invention have found that if the proportion of tricoordinate boron is too high, the decomposition of precipitates at low temperatures is promoted, and grains oriented other than the Goss orientation are easy to grow. In addition, the inventors of the present invention have found that by increasing the proportion of Al compounds that are inhibitors with low reactivity at low temperatures, it is possible to maintain Al compounds at low temperatures, allowing Goss-oriented grains to grow more preferentially.

[0018] On the other hand, if the precipitate remains, the magnetic properties may deteriorate. For example, if the amount of boron is excessive, boron nitride may be generated to deteriorate the magnetic properties. In addition, if the amount of Al is excessive, Al cannot be removed, and the magnetic properties may deteriorate due to Al.

[0019] Based on the above findings, the present inventors have found that the amount of tricoordinated boron and the amount of Al have appropriate ranges. Furthermore, the present inventors have found that the B content and particle size also have an influence on the reactivity, and have completed the present invention as a result of intensive studies.

[0020] The gist of the present invention completed based on the above findings is as follows.

[0021] [1] A mixed powder according to one embodiment of the present invention is a mixed powder for use as an annealing separator with MgO as the main agent, the mixed powder containing Al and B, the Al content of the mixed powder as a whole being 0.0007 mass % or more and 0.050 mass % or less, the B content of the mixed powder as a whole being 0.005 mass % or more and 0.040 mass % or less, the B containing tricoordinate boron, the average particle size of the mixed powder being 0.08 μm or more and 9.0 μm or less, and satisfying the following formula (1).

[0022] 0.06≤[Al] / [BO3]<5.00 (1)

[0023] In the above formula (1), [Al] is the Al content (mass %) in the mixed powder, and [BO3] is the content (mass %) of the above-mentioned tricoordinate boron in the mixed powder.

[0024] [2] In the mixed powder described in [1] above, the ratio of the tricoordinate boron in the B is preferably 5 mass % or more and less than 70 mass %.

[0025] [3] The mixed powder described in [1] or [2] above preferably contains one or more selected from the group consisting of Cl: 0.0005 mass % to 0.0300 mass % and Ti: 0.25 mass % to 5.00 mass %.

[0026] [4] The mixed powder according to any one of [1] to [3] above preferably contains 0.0005 mass % or more and 0.0300 mass % or less of Cl.

[0027] [5] The mixed powder according to any one of [1] to [4] above preferably contains 0.25 mass % to 5.00 mass % of Ti.

[0028] [6] The mixed powder described in any one of [1] to [5] above may contain MgO particles mainly composed of MgO, B-containing particles containing B, and Al-containing particles containing Al.

[0029] [7] In addition, another embodiment of the present invention is a MgO particle containing Al and B, wherein the Al content is greater than 0.0007 mass % and less than 0.0500 mass %, and the B content is greater than 0.005 mass % and less than 0.040 mass %, and the above-mentioned B contains tri-coordinated boron. The average particle size of the above-mentioned MgO particles is greater than 0.08 μm and less than 9.0 μm, and satisfies the following formula (1).

[0030] 0.06≤[Al] / [BO3]<5.00 (1)

[0031] In the above formula (1), [Al] is the Al content (mass %) in the MgO particles, and [BO 3 ​​] is the content (mass %) of the above-mentioned tricoordinate boron in the MgO particles.

[0032] [8] In a method for producing a grain-oriented electrical steel sheet according to another aspect of the present invention, an annealing separator comprising the mixed powder described in any one of [1] to [6] or the MgO particles described in [7] is used.

[0033] [9] In addition, in another embodiment of the present invention, in a method for producing MgO particles, a raw material powder comprising Mg-containing raw material particles containing one or more selected from magnesium hydroxide, basic magnesium carbonate and magnesium carbonate, B-containing raw material particles containing B and Al-containing raw material particles containing Al are sintered in air or a nitrogen atmosphere at a temperature of 700°C to 1100°C.

[0034]

[10] In the method for producing MgO particles described in [9] above, the content of tricoordinate boron relative to the mass of the raw material powder may be 0.010 mass % or more and 0.040 mass % or less.

[0035]

[11] In addition, in another embodiment of the present invention, in a method for producing MgO particles, raw material particles containing B and Al and containing one or more selected from magnesium hydroxide, basic magnesium carbonate and magnesium carbonate are sintered in air or nitrogen atmosphere at a temperature of 700°C to 1100°C.

[0036]

[12] In the method for producing MgO particles according to

[11] , the content of tricoordinate boron relative to the mass of the raw material particles may be 0.010 mass % or more and 0.040 mass % or less.

[0037]

[13] In addition, in another embodiment of the present invention, in a method for producing a mixed powder, a raw material powder comprising Mg-containing raw material particles containing one or more selected from magnesium hydroxide, basic magnesium carbonate and magnesium carbonate, B-containing raw material particles containing B and Al-containing raw material particles containing Al are sintered in air or a nitrogen atmosphere at a temperature of 700°C to 1100°C.

[0038]

[14] In the method for producing a mixed powder described in

[13] above, the content of tricoordinate boron relative to the mass of the raw material powder may be 0.010 mass % or more and 0.040 mass % or less.

[0039] Effects of the Invention

[0040] According to the present invention, there can be provided a mixed powder, MgO particles, a method for producing a oriented electrical steel sheet, a method for producing MgO particles, and a method for producing a mixed powder for suppressing the generation of coating defects due to the use of boron and producing a oriented electrical steel sheet having excellent appearance characteristics. DETAILED DESCRIPTION

[0041] <Mixed powder>

[0042] A mixed powder according to one embodiment of the present invention is a mixed powder for an annealing separator with MgO as the main agent, the mixed powder contains Al and B, the Al content of the mixed powder as a whole is greater than 0.0007 mass% and less than 0.050 mass%, the B content of the mixed powder as a whole is greater than 0.005 mass% and less than 0.040 mass%, the B contains tri-coordinated boron, the average particle size of the mixed powder is greater than 0.08 μm and less than 9.0 μm, and satisfies the following formula (1).

[0043] 0.06≤[Al] / [BO3]<5.00 (1)

[0044] In the above formula (1), [Al] is the content (mass %) of Al in the mixed powder, and [BO3] is the content (mass %) of the above tricoordinate boron in the mixed powder.

[0045] The mixed powder of the present embodiment contains MgO as a main component. The mixed powder contains, for example, 50.0 mass % or more of MgO. The proportion of MgO in the mixed powder is preferably 80.0 mass % or more, and more preferably 90.0 mass % or more.

[0046] The mixed powder contains MgO particles, but the MgO particles contained in the mixed powder are not limited to the MgO particles of one embodiment of the present invention described below, and for example, MgO particles having a MgO ratio of 50.0 mass % or more in the mixed powder can be used.

[0047] [Al content is 0.0007 mass % or more and 0.050 mass % or less]

[0048] The mixed powder contains Al. When the Al content contained in the mixed powder as a whole is less than 0.0007 mass%, the amount of Al that fixes nitrogen is reduced and the appearance of the coating is deteriorated. On the other hand, when the Al content contained in the mixed powder as a whole exceeds 0.050 mass%, the magnetic properties are deteriorated. Therefore, the Al content contained in the mixed powder as a whole is greater than 0.0007 mass% and less than 0.050 mass%. The Al content contained in the mixed powder as a whole can be greater than 0.003 mass%, greater than 0.004 mass% or greater than 0.005 mass%. In addition, the Al content contained in the mixed powder as a whole can be less than 0.045 mass%, less than 0.040 mass% or less than 0.030 mass%.

[0049] The mixed powder includes, for example, Al-containing particles containing Al. The Al-containing particles include an Al compound, and examples of the Al compound include Al2O3, AlN, Al(OH)3, and AlO(OH).

[0050] The mixed powder of this embodiment contains boron (B). The mixed powder, for example, contains B-containing particles containing B. The B-containing particles may contain at least one of pure boron and a B compound, and examples of the B compound include Na2B4O7, borax, calcium borate, magnesium borate, and the like.

[0051] [B content is 0.005 mass % or more and 0.040 mass % or less]

[0052] The mixed powder contains 0.005 mass % or more and 0.040 mass % or less of boron (B). When the B content is less than 0.005 mass %, the boron is insufficient, and thus the structure of the film is not strengthened, and the film is destroyed when the gas is released from the steel sheet, so the appearance of the grain-oriented electrical steel sheet is deteriorated. In addition, when the B content is less than 0.005 mass %, the thickness of the film becomes uneven due to insufficient boron, and thus the film tension of the grain-oriented electrical steel sheet is deteriorated. The B content is preferably 0.008 mass % or more, and more preferably 0.010 mass % or more.

[0053] On the other hand, when the B content in the mixed powder exceeds 0.040 mass%, the heat resistance of the internal oxide layer is too high, and the penetration of gas elements such as nitrogen in the steel sheet that become gas at the temperature during the final annealing into the atmosphere is excessively hindered. As a result, the gas pressure is excessively increased, and the film is destroyed and the gas is released, thereby deteriorating the appearance of the grain-oriented electrical steel sheet. Therefore, the B content in the mixed powder is set to 0.040 mass% or less. The B content is preferably 0.035 mass% or less, and more preferably 0.030 mass% or less.

[0054] The Al content and B content of the mixed powder were obtained by quantitative analysis using inductively coupled plasma mass spectrometry (ICP-MS). When quantitative analysis was performed using ICP-MS, the mixed powder was dissolved in a mixed acid of hydrochloric acid and nitric acid. At this time, if there was a residue left after the dissolution, the residue was recovered and dissolved in an alkaline solution for analysis.

[0055] [0.06≤[Al] / [BO3]<5.00]

[0056] The boron contained in the mixed powder exists in the form of tricoordinate boron (BO3) and tetracoordinate boron (BO4). Tricoordinate boron refers to boron with three oxygen atoms coordinated around the boron atom and a tricoordinate structure, and tetracoordinate boron refers to boron with four oxygen atoms coordinated around the boron atom and a tetracoordinate structure. Boron other than tricoordinate boron exists in the form of tetracoordinate boron.

[0057] The reaction of tricoordinate boron and tetracoordinate boron was investigated, and it was found that tricoordinate boron and tetracoordinate boron had different effects on film defects and appearance characteristics. Specifically, tricoordinate boron promotes film formation more than tetracoordinate boron, and has a greater impact on the decomposition of precipitates. In addition, it was found that if the amount of tricoordinate boron is too much, the reaction of film formation and decomposition of precipitates is too concentrated at low temperatures, and film destruction caused by gas release occurs. Therefore, it was found that by staggering the decomposition timing of precipitates, film destruction can be prevented, and a good film can be formed. The smaller the particle size or the higher the tricoordinate boron rate, the more the decomposition of precipitates caused by film formation at low temperatures is promoted.

[0058] When the content of the tricoordinated boron contained in the mixed powder and the content of Al contained in the mixed powder satisfy the following formula (1), the secondary recrystallization of the grain-oriented electrical steel sheet can be improved and the adverse effect on purification can be suppressed.

[0059] 0.06≤[Al] / [BO3]<5.00 (1)

[0060] In the above formula (1), [Al] is the Al content (mass %) in the mixed powder, and [BO3] is the content (mass %) of the above-mentioned tricoordinate boron in the mixed powder.

[0061] When [Al] / [BO3] is less than 0.06, the amount of Al that fixes nitrogen is insufficient in the relatively low temperature stage during secondary recrystallization, so the gas release suppression effect of BO3 on the coating becomes too strong, and the coating accompanied by gas release in the low temperature stage is easily destroyed, so that the oxide film on the surface of the steel sheet has an uneven appearance, and the appearance of the grain-oriented electrical steel sheet is deteriorated. [Al] / [BO3] is preferably 0.08 or more, and more preferably 0.15 or more.

[0062] On the other hand, when [Al] / [BO3] is 5.00 or more, less BN is formed, so more Al nitrides are formed, and Al nitrides are maintained until the high temperature stage during secondary recrystallization. These nitrides decompose at high temperatures, and the nitrogen generated by the decomposition of the nitrides destroys the film with low strength due to less BO3 and is released, so the appearance of the grain-oriented electrical steel sheet deteriorates. [Al] / [BO3] is preferably 4.5 or less, and more preferably 4.0 or less.

[0063] The content of tricoordinate boron [BO 3 ​​] in the mixed powder is determined by multiplying the B content determined by ICP-MS by the ratio of tricoordinate boron in B determined by the method described below.

[0064] [The ratio of tricoordinate boron in B is 5 mass % or more and less than 70 mass %]

[0065] The mixed powder preferably contains tricoordinate boron in an amount of 5 mass % or more and less than 70 mass % relative to the content of B in the mixed powder. When the proportion of tricoordinate boron in B is 5 mass % or more, the magnetic properties and coating properties can be improved. The proportion of tricoordinate boron in B is more preferably 8 mass % or more.

[0066] On the other hand, when the ratio of tricoordinate boron in B is 70% by mass or more, the reactivity becomes too high, which promotes the decomposition of precipitates, and sometimes the grains tend to grow in an orientation other than the Goss orientation. As a result, the magnetic properties are sometimes reduced. The ratio of tricoordinate boron in B is more preferably 50% by mass or less. In addition, tricoordinate boron is mainly contained in the above-mentioned B-containing particles, but may also be contained in MgO particles and Al-containing particles.

[0067] The ratio of tricoordinate boron in B contained in the mixed powder is determined by the following method. The measurement is performed using NMR (Nuclear Magnetic Resonance), and in the obtained spectrum, the peak in the range of less than 27 ppm and more than 6 ppm is defined as tricoordinate boron, and the peak in the range of less than 6 ppm and more than -6 ppm is defined as tetracoordinate boron, and the value obtained by dividing the integrated area of ​​the peak of tricoordinate boron by the total integrated area of ​​the integrated area of ​​the peak of tricoordinate boron and the integrated area of ​​the peak of tetracoordinate boron is defined as the ratio of tricoordinate boron in B.

[0068] The Al content in the mixed powder was quantitatively analyzed by ICP-MS using the above-mentioned method.

[0069] [Cl: 0.0005 mass % or more and 0.0300 mass % or less]

[0070] Cl (chlorine) is an element that improves reactivity with SiO2 formed on the surface of the steel sheet after decarburization annealing. It is preferred that the mixed powder of this embodiment contain 0.0005 mass % or more of Cl, because the coating properties are further improved. The Cl content is more preferably 0.0008 mass % or more.

[0071] On the other hand, when the Cl content exceeds 0.0300 mass%, desulfurization may be excessively inhibited due to the intensity of its oxide dissolution effect. If the Cl content is 0.0300 mass% or less, desulfurization can be sufficiently inhibited. Therefore, the Cl content is preferably 0.0300 mass% or less. The Cl content is more preferably 0.0250 mass% or less.

[0072] [One or more selected from Ca, Sr and Ba in a total amount of 0.02 mass% to 4.00 mass%]

[0073] Ca (calcium), Sr (strontium) and Ba (barium), like Cl, are elements that improve reactivity with SiO 2. Therefore, by containing a total of 0.02 mass % or more of one or more selected from Ca, Sr and Ba, adhesion is further improved, which is preferred.

[0074] On the other hand, when the total content of one or more selected from Ca, Sr and Ba exceeds 4.00 mass%, desulfurization of the steel sheet may be caused due to the strength of the sulfidation tendency. If the total content of one or more selected from Ca, Sr and Ba is 4.00 mass% or less, desulfurization can be sufficiently suppressed. Therefore, the total content of one or more selected from Ca, Sr and Ba is preferably 4.00 mass% or less.

[0075] Ca may be included in the mixed powder as a Ca compound. Examples of the Ca compound include calcium sulfate, hemihydrate gypsum, plaster of Paris, and gypsum. Sr may be included in the mixed powder as an Sr compound. Examples of the Sr compound include strontium sulfate. Ba may be included in the mixed powder as a Ba compound. Examples of the Ba compound include barium sulfate. Cl, Sr, and Ba may be included in the mixed powder as particles mainly containing each, or may be included in the above-mentioned particles constituting the mixed powder.

[0076] [Ti: 0.25 mass% or more and 5 mass% or less]

[0077] Ti (titanium) is an element that, as an oxide or after becoming an oxide in the initial stage of final annealing, adjusts the oxygen partial pressure in the annealing atmosphere at high temperature to about the decomposition oxygen partial pressure of TiO2, thereby contributing to increasing the amount of film formed. The above effect can be obtained by making the mixed powder of this embodiment contain 0.25% by mass or more of Ti. The Ti content is more preferably 0.5% by mass or more.

[0078] On the other hand, if the Ti content is 5% by mass or less, the deterioration of magnetic properties caused by excessive oxygen release can be suppressed. Therefore, the Ti content is preferably 5% by mass or less. The Ti content is more preferably 4% by mass or less.

[0079] Ti can be contained in the mixed powder in the form of, for example, TiO 2 , titanate, titanium boride, titanium nitride, or BaTiO 3. Ti can be contained in the mixed powder in the form of particles mainly containing the respective compounds, or in the above particles constituting the mixed powder.

[0080] The contents of Cl, Ca, Sr, Ba and Ti were quantitatively analyzed using ICP-MS by the above method.

[0081] [Impurities]

[0082] The components other than the above in the mixed powder of the present embodiment are MgO and impurities. Examples of impurities include Fe and Si. If the content of each impurity element is 0.5 mass % or less, or the total content is 1.0 mass % or less, the influence on the magnetic properties or coating properties of the grain-oriented electrical steel sheet is small.

[0083] [Average particle size of mixed powder]

[0084] The average particle size of the mixed powder is 0.08 μm or more and 9.0 μm or less in terms of the equivalent circular average particle size based on volume. When the average particle size of the mixed powder is less than 0.08 μm, it cannot prevent the steel plates from sticking to each other as an annealing separator, the formation of the coating becomes incomplete, and the magnetic properties deteriorate. In addition, when the average particle size of the mixed powder is less than 0.08 μm, the formation of the coating becomes incomplete, and the appearance deteriorates. In addition, when the average particle size of the mixed powder is less than 0.08 μm, the formation of the coating becomes incomplete, and the coating tension deteriorates. The average particle size of the mixed powder is preferably greater than 0.2 μm. On the other hand, when the average particle size of the mixed powder exceeds 9.0 μm, the reactivity with the steel plate is low, so the formation of the coating is insufficient. The average particle size of the mixed powder is preferably less than 7.0 μm, and more preferably less than 6.0 μm.

[0085] The average particle size of the mixed powder was measured by using a laser diffraction particle size distribution measuring device (HORIBA Co., Ltd., (device name) LA-920) to measure the particle size distribution of the volume frequency, and the average particle size under the equivalent circle diameter was taken as the average particle size of the mixed powder. The refractive index was set to 1.74, and a dispersion treatment using ultrasound was performed in pure water to measure the average particle size of the mixed powder.

[0086] <Method for producing mixed powder>

[0087] The mixed powder of the present embodiment described above is manufactured by sintering raw material powders including Mg-containing raw material particles containing one or more selected from magnesium hydroxide, basic magnesium carbonate and magnesium carbonate, B-containing raw material particles containing B and Al-containing raw material particles containing Al at a temperature of 700°C to 1100°C in air or a nitrogen atmosphere.

[0088] The B-containing raw material particles include Mg-containing raw material particles, boron, boric acid, magnesium boride, sodium borate, borax, etc. The B-containing raw material particles contain, for example, 0.01 mass % or more of B.

[0089] The Al-containing raw material particles include Mg-containing raw material particles, Al2O3, AlN, KAl(SO4)2·12H2O, Al(OH)3, AlO(OH), etc. The Al-containing raw material particles contain, for example, 0.01 mass % or more of Al.

[0090] The particle sizes of the Mg-containing raw material particles, Al-containing raw material particles, and B-containing raw material particles constituting the raw material powder may be, for example, a particle size that can obtain the average particle size of the mixed powder, or a particle size larger than the average particle size. When the particle size of the raw material powder is larger than the average particle size of the mixed powder, the mixed powder obtained by sintering by a known method may be crushed or classified. The particle sizes of the Mg-containing raw material particles, the Al-containing raw material particles, and the B-containing raw material particles may be, for example, greater than 0.08 μm or greater than 0.10 μm. In addition, the particle sizes of the Mg-containing raw material particles, the Al-containing raw material particles, and the B-containing raw material particles may be, for example, less than 15 μm or less than 10 μm.

[0091] In addition, the raw material powder may contain Cl, Ca, Sr, Ba and Ti as appropriate. When the raw material powder contains these elements, one or more of these elements may be contained in one particle.

[0092] The Al content in the raw material powder is preferably 0.0007% by mass or more and 0.050% by mass or less. If the Al content of the raw material particles is 0.0007% by mass or more and 0.050% by mass or less, the Al content of the manufactured mixed powder can be 0.0007% by mass or more and 0.050% by mass or less. The Al content in the raw material powder can be 0.003% by mass or more, 0.004% by mass or more, or 0.005% by mass or more. In addition, the Al content in the raw material powder can be 0.045% by mass or less, 0.040% by mass or less, or 0.030% by mass or less. However, in the case where the raw material powder contains a component that volatilizes by sintering, the Al content in the raw material powder is adjusted in consideration of its component amount.

[0093] Al is mainly contained in the above-mentioned Al-containing raw material particles, but may be contained in other particles constituting the raw material powder, for example, Mg-containing raw material particles, B-containing raw material particles, Ti-containing particles, and the like.

[0094] The B content in the raw material powder is preferably 0.005 mass % or more and 0.040 mass % or less. If the B content of the raw material particles is 0.005 mass % or more and 0.040 mass % or less, the B content of the manufactured mixed powder can be 0.005 mass % or more and 0.040 mass % or less. The B content is preferably 0.006 mass % or more, more preferably 0.008 mass % or more. In addition, the B content is more preferably 0.036 mass % or less, and further preferably 0.032 mass % or less. However, in the case where the raw material powder contains a component that volatilizes by sintering, the B content in the raw material powder is adjusted in consideration of its component amount.

[0095] B is mainly contained in the above-mentioned B-containing raw material particles, but may be contained in other particles constituting the raw material powder, for example, Mg-containing raw material particles, Al-containing raw material particles, Ti-containing particles, and the like.

[0096] The Al content and the B content in the raw material powder were quantitatively analyzed by ICP-MS according to the above-mentioned method.

[0097] The content of tricoordinate boron relative to the mass of the raw material powder is preferably 0.005 mass % or more and 0.040 mass % or less, and more preferably 0.010 mass % or more and 0.030 mass % or less. The content of tricoordinate boron in the raw material powder is preferably 5 mass % or more and 70 mass % or less relative to the B content. If the content of tricoordinate boron relative to the mass of the raw material powder or the content of tricoordinate boron relative to the B content is within the above range, the tricoordinate boron in the mixed powder after sintering more reliably satisfies the above formula (1).

[0098] The content of three-coordinated boron [BO3] in the raw material powder is obtained by multiplying the B content quantified by ICP-MS by the ratio of three-coordinated boron in B determined by the method described above.

[0099] The raw material powder is fired at a temperature of 700 °C or higher and 1100 °C or lower in an air atmosphere or a nitrogen atmosphere.

[0100] When the firing atmosphere is other than an air atmosphere or a nitrogen atmosphere, it is economically disadvantageous and thus not preferred.

[0101] In addition, when the firing temperature is less than 700 °C, the firing becomes insufficient. Therefore, the firing temperature is set to 700 °C or higher. The firing temperature is preferably 720 °C or higher, more preferably 750 °C or higher. On the other hand, by making the firing temperature 1100 °C or lower, the chemical structure of the fired three-coordinated boron can be stabilized, and the ratio of three-coordinated boron in the mixed powder can be increased without significantly changing the particle size. Therefore, the firing temperature is 1100 °C or lower. The firing temperature is preferably 1080 °C or lower, more preferably 1040 °C or lower.

[0102] The firing time can be set, for example, to 5 minutes or more and 120 minutes or less. From the viewpoint of eliminating firing unevenness, the firing time is preferably 8 minutes or more, more preferably 10 minutes or more. On the other hand, from the economic viewpoint, the firing time is preferably 80 minutes or less, more preferably 60 minutes or less.

[0103] Thus, the manufacturing method of the mixed powder has been described.

[0104] In the above manufacturing method of the mixed powder, on the premise that the particles serving as the Mg source, the particles serving as the B source, and the particles serving as the Al source are different from each other, the way in which the raw material powder contains Mg-containing raw material particles, B-containing raw material particles, and Al-containing raw material particles has been described. However, it is not limited to this way. The Mg-containing raw material particles serving as the Mg source may contain B and / or Al in a manner serving as the B source and / or the Al source, and may also contain other elements. The B-containing raw material particles may contain Al and may also contain other elements.

[0105] In addition, the mixed powder of the present embodiment described above can also be manufactured by mixing MgO particles, Al-containing particles, and B-containing particles containing three-coordinated boron in such a way that MgO is the main agent, the B content is 0.005 mass% or more and 0.040 mass% or less, the average particle size is 0.08 μm or more and 9.0 μm or less, and the above formula (1) is satisfied.

[0106] <MgO particles>

[0107] The MgO particles of one embodiment of the present invention contain Al and B, the Al content is 0.0007% by mass or more and 0.050% by mass or less, the B content is 0.005% by mass or more and 0.040% by mass or less, the above B contains trivalent boron, and the average particle size of the above MgO particles is 0.08 μm or more and 9.0 μm or less, satisfying the following formula (1).

[0108] 0.06 ≤ [Al] / [BO3] < 5.00 (Formula (1))

[0109] In the above formula (1), [Al] is the Al content (mass%) in the MgO particles, and [BO3] is the content (mass%) of the above trivalent boron in the MgO particles.

[0110] The above characteristics of the MgO particles of this embodiment are the same as those of the above mixed powder, so the detailed description here is omitted. In addition, in the MgO particles of this embodiment, similar to the mixed powder, the proportion of the above trivalent boron in B is preferably 5% by mass or more and less than 70% by mass. In addition, the MgO particles, similar to the mixed powder, preferably contain 0.0005% by mass or more and 0.0300% by mass or less of Cl. In addition, the MgO particles, similar to the mixed powder, preferably contain 0.25% by mass or more and 5.0% by mass or less of Ti. Herein, the MgO particles containing the above components means that the above components are contained in the MgO particles constituting the MgO powder, and it means that particles other than the MgO particles do not exist alone.

[0111] <Manufacturing method of MgO particles>

[0112] The above MgO particles are manufactured by the following manufacturing method (I) or (II).

[0113] (I)

[0114] The raw material powder containing Mg-containing raw material particles selected from one or more of magnesium hydroxide (Mg(OH)2), basic magnesium carbonate (mMgCO3·Mg(OH)2·nH2O), and magnesium carbonate (Mg(CO3)), B-containing raw material particles containing B, and Al-containing raw material particles containing Al is fired at a temperature of 700°C or more and 1100°C or less in air or a nitrogen atmosphere.

[0115] (II)

[0116] The raw material particles containing B and Al and selected from one or more of magnesium hydroxide, basic magnesium carbonate, and magnesium carbonate are fired at a temperature of 700°C or more and 1100°C or less in air or a nitrogen atmosphere.

[0117] Hereinafter, each manufacturing method will be described.

[0118] [Manufacturing method (I)]

[0119] The manufacturing method (I) is a method for manufacturing MgO particles by sintering a raw material powder containing Mg-containing raw material particles containing one or more selected from magnesium hydroxide, basic magnesium carbonate and magnesium carbonate, B-containing raw material particles containing B and Al-containing raw material particles containing Al in air or nitrogen atmosphere at a temperature of 700°C to 1100°C. In the case where the raw material powder contains components that volatilize by sintering, the Al content and the B content are adjusted in consideration of the amount of the components. This manufacturing method is basically the same as the manufacturing method of the mixed powder mentioned above. However, in the manufacturing method of the mixed powder mentioned above, this manufacturing method is different from the manufacturing method of the mixed powder mentioned above in that oxides other than B and Al that are not dissolved or contained as impurities are sometimes mixed in the MgO particles and sintered.

[0120] [Production method (II)]

[0121] In the production method (II), raw material particles containing B and Al and containing one or more selected from magnesium hydroxide, basic magnesium carbonate and magnesium carbonate are fired in air or nitrogen atmosphere at a temperature of 700° C. to 1100° C. When the raw material powder contains a component that volatilizes by firing, the Al content and the B content are adjusted in consideration of the component amount.

[0122] The raw material particles containing at least any one of magnesium hydroxide, basic magnesium carbonate and magnesium carbonate contain B and Al. The Al content is 0.0007% by mass or more and 0.050% by mass or less. If the Al content of the raw material particles is 0.0007% by mass or more and 0.050% by mass or less, the Al content of the manufactured MgO particles can be 0.0007% by mass or more and 0.050% by mass or less. The Al content of the raw material particles can be 0.003% by mass or more, 0.004% by mass or more or 0.005% by mass or more. In addition, the Al content of the raw material particles can be 0.045% by mass or less, 0.040% by mass or less or 0.030% by mass or less.

[0123] The B content is preferably 0.005 mass % or more and 0.040 mass % or less. If the B content of the raw material particles is 0.005 mass % or more and 0.040 mass % or less, the B content of the manufactured MgO particles can be 0.005 mass % or more and 0.040 mass % or less. The B content is more preferably 0.008 mass % or more, and further preferably 0.010 mass % or more. In addition, the B content is more preferably 0.035 mass % or less, and further preferably 0.030 mass % or less.

[0124] The content of tricoordinate boron in the raw material particles is preferably 5 mass % or more and 70 mass % or less relative to the content of B. If the content of tricoordinate boron is within the above range relative to the content of B, the tricoordinate boron in the MgO particles fired under the firing conditions described below satisfies the above formula (1).

[0125] In the raw material particles, the particle size of magnesium hydroxide, basic magnesium carbonate and magnesium carbonate can be, for example, a particle size that can obtain the average particle size of the above-mentioned MgO particles, or a particle size larger than the average particle size. In the case where the particle size of the raw material particles is larger than the average particle size of the MgO particles, the MgO particles obtained by calcining by a known method can be crushed. The particle size of magnesium hydroxide, basic magnesium carbonate and magnesium carbonate can be, for example, 0.05 μm or more or 0.08 μm or more. In addition, the particle size of magnesium hydroxide, basic magnesium carbonate and magnesium carbonate can be, for example, less than 12 μm or less than 10 μm.

[0126] The raw material particles are fired in air or nitrogen atmosphere at a temperature of 700° C. to 1100° C. The firing atmosphere, firing temperature and firing time are the same as those of the raw material powder, and thus detailed descriptions thereof are omitted.

[0127] <Method for producing grain-oriented electrical steel sheet>

[0128] A method for manufacturing a oriented electrical steel sheet according to an embodiment of the present invention uses the above-mentioned MgO particles or mixed powder as an annealing separator. The method for manufacturing a oriented electrical steel sheet according to the present embodiment can manufacture the oriented electrical steel sheet according to a manufacturing method including the following steps: a hot rolling step of hot rolling a steel billet to obtain a hot-rolled sheet; a hot-rolled sheet annealing step of annealing the hot-rolled sheet; a cold rolling step of cold-rolling the hot-rolled sheet after the hot-rolled sheet annealing step to obtain a cold-rolled sheet; a decarburization annealing step of decarburizing the cold-rolled sheet; and a final annealing step of applying an annealing separator containing the above-mentioned MgO particles or mixed powder to the cold-rolled sheet after the decarburization annealing step and drying it and then performing final annealing.

[0129] In the present embodiment, as an annealing separator applied before the final annealing, a slurry-like annealing separator is used by mixing the mixed powder of the present embodiment described above with water. When the mixed powder does not contain Ti, Ti may be further mixed. By using this annealing separator, a grain-oriented electrical steel sheet having excellent coating appearance and excellent coating adhesion can be manufactured.

[0130] In the above-mentioned production method, regarding the chemical composition of the steel slab and the conditions of each step, except for the annealing separator used, known production conditions for a grain-oriented electrical steel sheet can be applied.

[0131] When the annealing separator is prepared by mixing a mixed powder of MgO particles and TiO2 particles with water to form a slurry (in the case of preparing an aqueous slurry), the proportion of TiO2 when the mass of the mixed powder is set to 100% is preferably set to 0.25 to 5.0 mass % in terms of Ti content.

[0132] Example

[0133] Next, an embodiment of the present invention is shown. The conditions in the embodiment are an example of conditions used to confirm the feasibility and effect of the present invention. The present invention is not limited to the conditions used in the following embodiment. The present invention can adopt various conditions as long as it does not deviate from the gist of the present invention and achieves the purpose of the present invention.

[0134] <Example 1>

[0135] The oriented electromagnetic steel sheet is made using the MgO particles shown in Table 1 or the mixed powder of the MgO particles and TiO2 particles shown in Table 2. Specifically, an aqueous slurry containing an annealing separator of the MgO particles shown in Table 1 or the mixed powder shown in Table 2 is applied to the cold-rolled steel sheet after the primary recrystallization annealing. The aqueous slurry is prepared by mixing the MgO powder or the mixed powder with water. The content of the solid component (MgO particles or mixed powder) in the aqueous slurry is 20% by mass. For the cold-rolled steel sheet with the aqueous slurry coated on the surface, a sintering treatment is performed at 300°C for 30 seconds in any test number to dry the aqueous slurry and sinter the solid component. After sintering, a final annealing treatment is performed. In the final annealing treatment, it is kept at 1200°C for 20 hours in any test number. Through the above manufacturing process, a grain-oriented electrical steel sheet having a base steel sheet and a glass coating containing a composite oxide such as forsterite (Mg2SiO4) with a length of 300 mm in the longitudinal direction, a length of 60 mm in the sheet width direction, and a sheet thickness of 0.23 mm was manufactured. It should be noted that the "BO3 ratio" shown in Table 1 represents the ratio of tri-coordinated boron in B.

[0136] The B content, Al content and Cl content of the MgO particles and the mixed powder are measured using inductively coupled plasma mass spectrometry (ICP-MS). In detail, a solution prepared by dissolving the MgO particles or the mixed powder in a mixed acid of hydrochloric acid and nitric acid is used. In the case where a residue remains, the residue is recovered and dissolved in an alkaline solution for analysis. In addition, the proportion of tricoordinate boron in B is obtained by the following method. The measurement is performed by NMR, and in the obtained spectrum, the peak in the range of less than 27 ppm and more than 6 ppm is regarded as tricoordinate boron, the peak in the range of less than 6 ppm and more than -6 ppm is regarded as tetracoordinate boron, and the integral area of ​​the peak of tricoordinate boron is divided by the integral area of ​​the peak of tricoordinate boron and the integral area of ​​the peak of tetracoordinate boron. The value obtained is the proportion of tricoordinate boron in B. The BO3 content [BO3] of the MgO particles and the mixed powder is obtained by multiplying the B content quantified by ICP-MS by the proportion of tricoordinate boron in B.

[0137] The obtained grain-oriented electrical steel sheets were evaluated for magnetic properties (B8), appearance, and coating tension according to the following procedures.

[0138] [Magnetic properties]

[0139] The magnetic properties of each grain-oriented electrical steel sheet were evaluated by the following method.

[0140] Specifically, a magnetic field of 800 A / m was applied to a sample having a rolling direction length of 300 mm and a width of 60 mm, and the magnetic flux density B8 was determined. When B8 was 1.92 T or more, it was determined that the magnetic properties were good.

[0141] [Appearance]

[0142] The color tone of the sample with a rolling direction length of 50 mm and a width of 60 mm cut from the center of the rolling direction length of each oriented electromagnetic steel sheet was evaluated, and then a known insulating film was formed to evaluate the coating defects. When the color tone of the primary coating before the insulating coating of each oriented electromagnetic steel sheet is uniform and there are no coating defects (holes and rust) after the insulating coating is formed, the appearance is judged to be excellent. Specifically, the evaluation is performed as follows.

[0143] A: The color tone before the insulation coating is formed is uniform, and the maximum area of ​​the coating defect after the insulation coating is formed is less than 2mm 2

[0144] B: The color tone before the insulation coating is formed is uniform, and the maximum area of ​​the coating defect after the insulation coating is formed is 2 mm 2 Above and less than 4mm 2

[0145] C: The color tone before the insulation coating is formed is uniform, and the maximum area of ​​the coating defect after the insulation coating is formed is 4 mm 2 Above and less than 6mm 2

[0146] D: The color tone before the insulation coating is formed is uneven, or the maximum area of ​​the coating defect after the insulation coating is formed is 6mm 2 above

[0147] An evaluation of A or B is judged as passing.

[0148] [Laminating tension]

[0149] For samples with a rolling direction length of 300 mm and a width of 60 mm, the coating tension is calculated from the curvature radius of the steel plate after only one side of the sample is pickled to remove the coating. The coating tension according to the curvature radius can be calculated by a known method, such as the method disclosed in the "Post-Evaluation Report on the Development of Innovative Magnetic Materials for Reducing Power Losses in Transformers" (February 2001) by the Research and Evaluation Committee of the New Energy and Industrial Technology Development Organization, an independent administrative agency.

[0150] If the lamination tension is 350g / mm 2 The results are shown in Tables 1 and 2.

[0151]

[0152]

[0153] In the example of No. 1, the average grain size was too small, so the film formation became uneven, and the B8, appearance, and film tension of the grain-oriented electrical steel sheet were inferior.

[0154] In the example of No. 2, the average grain size was too large, so the amount of film formed was too small, and B8, appearance, and film tension of the grain-oriented electrical steel sheet were inferior.

[0155] In the case of No. 6, since the B content was too low, B8, appearance, and coating tension were inferior.

[0156] In the example of No. 7, since the B content was too high, the appearance of the grain-oriented electrical steel sheet was inferior.

[0157] In Examples No. 10, 11, 24, and 27, the [Al] / [BO3] value was outside the range of the above formula (1), and B8 and appearance of the grain-oriented electrical steel sheets were inferior.

[0158] In Examples No. 16 and 29, Al exceeded 0.050 mass %, and B8 of the grain-oriented electrical steel sheets became inferior.

[0159] In the example of No. 28, Al was less than 0.0007 mass %, and B8 and appearance of the grain-oriented electrical steel sheet were inferior.

[0160] In the examples of No. 3 to 5, 8, 9, 12 to 15, 17 to 23, 25, and 26, the average grain size was in the range of 0.08 μm to 9.0 μm, the Al content was in the range of 0.0007 mass % to 0.050 mass %, the B content was in the range of 0.005 mass % to 0.040 mass %, and the [Al] / [BO3] value was in the range of the above formula (1), and the grain-oriented electrical steel sheets with excellent magnetic properties, appearance, and coating tension were obtained. The [Al] / [BO3] values ​​of No. 3 to 5, 8, 9, 14, 15, and 17 to 23 were within the range of 0.15 to 4.00, and thus the appearance characteristics were particularly excellent.

[0161] <Example 2>

[0162] A oriented electromagnetic steel sheet is manufactured using a mixed powder containing MgO particles, TiO2 particles and at least one of B compound particles or Al compound particles at a blending ratio shown in Table 3. Specifically, an aqueous slurry containing an annealing separator of the mixed powder of Table 3 is applied to the cold-rolled steel sheet after primary recrystallization annealing. The aqueous slurry is prepared by mixing the mixed powder of Table 3 with water. The content of the solid component (mixed powder) in the aqueous slurry is 20% by mass. For the cold-rolled steel sheet with the aqueous slurry coated on the surface, a sintering treatment is performed at 300°C for 30 seconds in any case to dry the aqueous slurry and sinter the solid component. After sintering, a final annealing treatment is performed. In the final annealing treatment, it is kept at 1200°C for 20 hours in any case. Through the above manufacturing process, as shown in Table 3, a oriented electrical steel sheet having a base steel sheet and a glass coating containing a composite oxide such as forsterite (Mg2SiO4), with a length of 300 mm in the longitudinal direction, a length of 60 mm in the sheet width direction, and a sheet thickness of 0.23 mm was manufactured.

[0163]

[0164] The B content, Al content, Cl content and BO3 content of the mixed powder, and the ratio of tricoordinated boron in B (BO3 ratio) were measured by the same method as in Example 1. In addition, the magnetic properties (B8), appearance and coating tension of the obtained grain-oriented electrical steel sheet were evaluated in the same manner as in Example 1. The results are shown in Table 4.

[0165] Table 4

[0166]

[0167] In Example No. 30, since the average particle size of the mixed powder was too small, the film formation became uneven, and the B8, appearance, and film tension of the grain-oriented electrical steel sheet were inferior.

[0168] In Example No. 31, since the average particle size of the mixed powder was too large, the film formation became uneven, and the B8, appearance, and film tension of the grain-oriented electrical steel sheet were inferior.

[0169] In the example of No. 34, the B content in the mixed powder was too small, so B8, appearance, and coating tension of the grain-oriented electrical steel sheet were inferior.

[0170] In the example of No. 35, the B content in the mixed powder was too high, and the appearance of the grain-oriented electrical steel sheet was inferior.

[0171] In Examples No. 36 to 39, the [Al] / [BO3] value was outside the range of the above formula (1), and the B8 and appearance of the grain-oriented electrical steel sheets were inferior.

[0172] In the examples of No. 32, 33, and 40, the average particle size was in the range of 0.08 μm to 9.0 μm, the Al content contained in the entire mixed powder was in the range of 0.0007 mass % to 0.050 mass %, the B content was in the range of 0.005 mass % to 0.040 mass %, and the [Al] / [BO3] value was in the range of the above formula (1), and the oriented electrical steel sheet with excellent magnetic properties, appearance, and coating tension was obtained. In addition, the [Al] / [BO3] values ​​of No. 32, 33, and 40 were within the range of 0.15 to 4.00, so the appearance characteristics were particularly excellent.

[0173] <Example 3>

[0174] The raw material powder and TiO2 particles shown in Table 5 were mixed and sintered under the conditions shown in Table 5 to prepare the mixed powder shown in Table 6. Using the prepared mixed powder, a grain-oriented electrical steel sheet was manufactured by the same method as in Example 1. It should be noted that, hereinafter, the powder obtained by sintering without mixing TiO2 particles may be referred to as MgO particles.

[0175] The B content, Al content, Cl content and BO3 content of the raw material powder, MgO particles and mixed powder, and the ratio of tricoordinate boron in B (BO3 ratio) were measured by the same method as in Example 1. In addition, the BO3 content relative to the mass of the raw material powder was obtained by multiplying the B content quantified by ICP-MS by the ratio of tricoordinate boron in B. For each of the produced grain-oriented electrical steel sheets, the magnetic properties (B8), appearance and coating tension were evaluated in the same manner as in Example 1. The results are shown in Table 6.

[0176]

[0177]

[0178] In Example No. 41, the B content in the obtained MgO particles was less than 0.005 mass %, and the grain-oriented electrical steel sheet produced using the MgO particles was inferior in appearance and coating tension.

[0179] In Example No. 42, the B content in the obtained MgO particles exceeded 0.040% by mass, and the appearance of the grain-oriented electrical steel sheet produced using the MgO particles was inferior.

[0180] In the examples of Nos. 43 and 44, the [Al] / [BO3] value of the obtained MgO particles was outside the range of the above formula (1), and the B8 and appearance of the grain-oriented electrical steel sheets were inferior.

[0181] In the examples of Nos. 45 to 51 and 54 to 57, the Al content contained in the whole MgO particles or mixed powder was 0.0007 mass% or more and 0.050 mass% or less, the B content was 0.005 mass% or more and 0.040 mass% or less, the average particle size of the MgO particles or mixed powder was 0.08 μm or more and 9.0 μm or less, and the [Al] / [BO3] value of the MgO particles or mixed powder was within the range of the above formula (1), and the grain-oriented electrical steel sheets with excellent magnetic properties, appearance and coating tension were obtained. In addition, the [Al] / [BO3] values ​​of Nos. 45 to 47, 49, 51, 54, 55 and 57 were within the range of 0.15 to 4.00, so the appearance characteristics were particularly excellent.

[0182] In the case of No. 52, the calcination temperature was too low, so the raw material powder was not sufficiently calcined, and MgO as the main agent could not be obtained.

[0183] In Example No. 53, since the firing temperature was too high, the particle size of the mixed powder became too large, and the appearance and coating tension of the grain-oriented electrical steel sheet became inferior.

[0184] <Example 4>

[0185] The raw material powders shown in Table 7 were fired under the conditions shown in Table 7 to prepare the mixed powders shown in Table 8. A grain-oriented electrical steel sheet was produced in the same manner as in Example 2 using the prepared mixed powders.

[0186] The B content, Al content, Cl content and BO3 content of the raw material powder and the mixed powder, and the ratio of tricoordinate boron in B (BO3 ratio) were measured by the same method as in Example 1. In addition, the BO3 content relative to the mass of the raw material powder was obtained by multiplying the B content quantified by ICP-MS by the ratio of tricoordinate boron in B. In addition, for each of the produced grain-oriented electrical steel sheets, the magnetic properties (B8), appearance and coating tension were evaluated in the same manner as in Example 1. The results are shown in Table 8.

[0187]

[0188]

[0189] As shown in Nos. 58 to 60, 63, 64, and 67 to 74, in the mixed powder produced using the raw material powder containing B and Al, the Al content contained in the whole mixed powder was 0.0007 mass% or more and 0.050 mass% or less, and the B content was 0.005 mass% or more and 0.040 mass% or less, and MgO particles satisfying the above formula (1) were obtained. As a result, a oriented electrical steel sheet having excellent magnetic properties, appearance, and coating tension was obtained. In addition, the [Al] / [BO3] values ​​of Nos. 58 to 60, 63, 64, and 67 to 74 were within the range of 0.15 to 4.00, so the appearance characteristics were particularly excellent.

[0190] In Examples No. 61 and 62, the [Al] / [BO3] value of the obtained mixed powder was outside the range of the above formula (1), and the B8 and appearance of the grain-oriented electrical steel sheet were inferior.

[0191] In the case of No. 65, the calcination temperature was too low, so the raw material powder was not sufficiently calcined, and MgO as the main component could not be obtained.

[0192] In Example No. 66, since the firing temperature was too high, the particle size of the mixed powder became too large, and the appearance and coating tension of the grain-oriented electrical steel sheet were inferior.

Claims

1. A mixed powder, which is a mixed powder for annealing separator with MgO as the main agent, The mixed powder contains Al and B, The Al content of the mixed powder as a whole is 0.0007 mass % or more and 0.050 mass % or less, The B content of the mixed powder as a whole is 0.005 mass % or more and 0.040 mass % or less, The B contains tricoordinate boron, The average particle size of the mixed powder is 0.08 μm or more and 9.0 μm or less. Satisfies the following formula (1): 0.06≤[Al] / [BO3]<5.00 (1) In the formula (1), [Al] is the Al content (mass %) in the mixed powder, and [BO3] is the content (mass %) of the tricoordinate boron in the mixed powder.

2. The mixed powder according to claim 1, wherein The ratio of the tricoordinate boron in the B is 5 mass % or more and less than 70 mass %.

3. The mixed powder according to claim 1 or 2, wherein: It contains one or two or more selected from the group consisting of Cl: 0.0005 mass % to 0.0300 mass % and Ti: 0.25 mass % to 5.00 mass %.

4. The mixed powder according to claim 3, wherein Contains 0.0005 mass % or more and 0.0300 mass % or less of Cl. The mixed powder according to claim 3 , comprising 0.25 mass % or more and 5.00 mass % or less of Ti.

6. The mixed powder according to claim 1 or 2, wherein: The mixed powder contains MgO particles mainly composed of MgO, B-containing particles containing B, and Al-containing particles containing Al.

7. MgO particles containing Al and B, The Al content is 0.0007 mass % or more and 0.050 mass % or less, The B content is 0.005 mass % or more and 0.040 mass % or less, The B contains tricoordinate boron, The average particle size of the MgO particles is 0.08 μm or more and 9.0 μm or less. Satisfies the following formula (1): 0.06≤[Al] / [BO3]<5.00 (1) In the formula (1), [Al] is the Al content (mass %) in the MgO particles, and [BO 3 ​​] is the content (mass %) of the tri-coordinated boron in the MgO particles.

8. A method for manufacturing a grain-oriented electrical steel sheet, wherein: An annealing separator comprising the mixed powder according to claim 1 or 2 or the MgO particles according to claim 7 is used.

9. A method for producing MgO particles, wherein: A raw material powder including Mg-containing raw material particles containing one or more selected from magnesium hydroxide, basic magnesium carbonate and magnesium carbonate, B-containing raw material particles containing B and Al-containing raw material particles containing Al is sintered at a temperature of 700° C. to 1100° C. in air or a nitrogen atmosphere.

10. The method for producing MgO particles according to claim 9, wherein: The content of tricoordinate boron relative to the mass of the raw material powder is 0.005 mass % or more and 0.040 mass % or less.

11. A method for producing MgO particles, wherein: Raw material particles containing B and Al and containing one or more selected from magnesium hydroxide, basic magnesium carbonate and magnesium carbonate are fired at a temperature of 700° C. to 1100° C. in air or a nitrogen atmosphere.

12. The method for producing MgO particles according to claim 11, wherein: The content of tricoordinate boron relative to the mass of the raw material particles is 0.005 mass % or more and 0.040 mass % or less.

13. A method for producing a mixed powder, wherein: A raw material powder including Mg-containing raw material particles containing one or more selected from magnesium hydroxide, basic magnesium carbonate and magnesium carbonate, B-containing raw material particles containing B and Al-containing raw material particles containing Al is sintered at a temperature of 700° C. to 1100° C. in air or a nitrogen atmosphere.

14. The method for producing a mixed powder according to claim 13, wherein: The content of tricoordinate boron relative to the mass of the raw material powder is 0.005 mass % or more and 0.040 mass % or less.

Citation Information

Patent Citations

  • Powder for annealing separation agent, production of the powder, and directive magnetic steel sheet

    JP2017128772A

  • Manufacturing method of powder for annealing separation agent

    JP2020015982A

  • Frequency sweep amount measuring device and method for optical frequency comb

    JP2022137911A